Pre-Service Teachers’ Coping and Anxiety within Mixed-Reality Simulations - Steven Anton; Jody S. Piro; Marcia A. B. Delcourt; Erik Gundel (Social Sciences, 2023)
The purpose of this study was to investigate the impact of time in Mixed-Reality Simulations (MRS) on anxiety levels and coping for pre-service teachers (PSTs). A convergent parallel mixed-methods design was utilized. For each pair of matched observations on both levels for both surveys, no statistically significant difference was found. Three finding statements emerged from the qualitative data: (a) participants experienced anxiety surrounding the mixed-reality simulations from many different sources, (b) participants’ anxiety surrounding the mixed-reality simulations manifested itself in a variety of ways, and (c) participants implemented different coping skills to attempt to manage the anxiety they were experiencing surrounding the mixed-reality simulations. A comparison of the quantitative and the qualitative findings revealed two mixed-method findings: (a) pre-service teachers can benefit from experiencing anxiety within a mixed-reality simulation setting and (b) mixed-reality simulations provide pre-service teachers with the opportunity to develop their coping skills. Implications for the potential benefits and impact of time spent within a mixed-reality simulator on pre-service teachers’ anxiety and adaptiveness in coping are addressed.